2022
DOI: 10.1038/s41598-022-09585-z
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular ultrasound-factors associated with slow flow following rotational atherectomy in heavily calcified coronary artery

Abstract: Intravascular ultrasound (IVUS) can provide useful information in patients undergoing complex percutaneous coronary intervention with rotational atherectomy (RA). The association between IVUS findings and slow flow following rotational atherectomy (RA) has not been investigated, although slow flow has been shown to be an unfavorable sign with worse outcomes. The aim of this study was to determine the IVUS-factors associated with slow flow just after RA. We retrospectively enrolled 290 lesions (5316 IVUS-frames… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…When performing PCI with RA for calcified lesions, the slow-flow phenomenon is frequently encountered [ 12 ]. Previous studies have reported that lesion length as measured angiographically was associated with the occurrence of slow flow after RA [ 7 , 17 ] and that the arc of calcification at the minimal lumen area derived from IVUS represents a new factor associated with slow flow after RA [ 18 ]. Furthermore, Sakakura et al showed that IVUS cross-ability was also significantly associated with slow flow after RA [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…When performing PCI with RA for calcified lesions, the slow-flow phenomenon is frequently encountered [ 12 ]. Previous studies have reported that lesion length as measured angiographically was associated with the occurrence of slow flow after RA [ 7 , 17 ] and that the arc of calcification at the minimal lumen area derived from IVUS represents a new factor associated with slow flow after RA [ 18 ]. Furthermore, Sakakura et al showed that IVUS cross-ability was also significantly associated with slow flow after RA [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because reverberations are closely associated with smooth surface of the calcified lesions [41], reverberations may be observed in the calcified lesions after RA as well as the unmodified calcified lesions with smooth surface. Recently, Jinnouchi, et al reported the association between slow flow following RA and reverberations [42]. However, the clinical significance of the natural reverberations has not sufficiently investigated.…”
Section: Aim Of Ramentioning
confidence: 99%
“…Lesion length and burr-to-artery ratio were reported as the determinants of slow flow [66,93]. Furthermore, IVUS findings such as longer lesion length, the maximum number of reverberations, and the greater arc of calcification at MLA may predict slow flow after RA [42].…”
Section: Complications: Slow Flowmentioning
confidence: 99%
“…Notably, IVUS may also assist in predicting, and thus avoiding, procedural complications such as the no- or slow-reflow phenomenon. Lesions associated with CAC extending >24 mm, an increase in the number of reverberations post-modification, and an arc of calcium at the minimum lumen area >300° were associated with increased rates of slow/no reflow and may alert physicians as to which patients may be at higher risk and might require preventative measures ( 16 ).…”
Section: Intravascular Ultrasoundmentioning
confidence: 99%